2003
DOI: 10.1007/s00213-002-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased extracellular serotonin level in rat hippocampus induced by chronic citalopram is augmented by subchronic lithium: neurochemical and behavioural studies in the rat

Abstract: The present results support the assumption that increases in hippocampal 5-HT neurotransmission may be important in the augmentatory effect of lithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 60 publications
6
30
0
Order By: Relevance
“…To our knowledge, an effect of chronic lithium in the FST has not been reported. Lithium does not affect time immobile for rats in the FST (Hata et al, 1995;Kitamura et al, 2002;Einat et al, 2003;Wegener et al, 2003). Acute lithium injection has been reported to reduce time immobile in mice if animals are tested 30 min after injection but not at 45 min (Nixon et al, 1994;Redrobe and Bourin, 1999a).…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, an effect of chronic lithium in the FST has not been reported. Lithium does not affect time immobile for rats in the FST (Hata et al, 1995;Kitamura et al, 2002;Einat et al, 2003;Wegener et al, 2003). Acute lithium injection has been reported to reduce time immobile in mice if animals are tested 30 min after injection but not at 45 min (Nixon et al, 1994;Redrobe and Bourin, 1999a).…”
Section: Discussionmentioning
confidence: 92%
“…Although our study did not examine the pharmacological mechanism of action of lithium that may be responsible for its synergistic effects, previous studies have reported a variety of actions of lithium on 5-HT systems. For example, there is evidence that chronic lithium treatment enhances the release of 5-HT and the sensitivity of postsynaptic 5-HT 1A receptors in the hippocampus, a main projection region from the MRN (Treiser et al, 1981;Wegener et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that subchronic lithium increased the anxiolytic-like effect of various serotonergic antidepressants in contextual conditioned fear Kitaichi et al, 2006;Muraki et al, 1999). Further, subchronic lithium treatment not only increases extracellular 5-HT concentrations at baseline in various brain regions but also increases the elevating effect of various antidepressants on extracellular 5-HT concentrations additively, suggesting that the augmentation effect of lithium is mediated by the facilitation of 5-HT neurotransmission (Kitaichi et al, , 2006Muraki et al, 2001;Wegener et al, 2003). Because a recent study reported that lithium moderates the manic-like behavioral alterations induced by an electrolytic lesion of the MRN in mice (Pezzato et al, 2015), the MRN is a candidate region for lithium augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical studies have demonstrated that lithium modifies serotonergic neurotransmission and increases extracellular serotonin (5-hydroxytryptamine; 5-HT) levels in the brain through several mechanisms, such as increased 5-HT synthesis, increased 5-HT turnover, and increased 5-HT release from nerve endings (Eroglu and Hizal, 1987;Kitaichi et al, 2004Kitaichi et al, , 2006Muraki et al, 2001;Price et al, 1990;Wegener et al, 2003). Preclinically, the combinations of lithium with selective serotonin reuptake inhibitors (SSRIs) or monoamine oxidase inhibitors have been reported to increase the effects of these antidepressants on extracellular 5-HT concentrations and on anxiety-like behaviors in the contextual fear conditioning test (Kitaichi et al, 2006;Muraki et al, 1999;Muraki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo microdialysis studies reported that the systemic administration of mirtazapine increased extracellular 5-HT concentrations in the hippocampus of rats (Yamauchi et al, 2012). In addition, subchronic lithium treatment increased extracellular 5-HT levels in the medial prefrontal cortex and hippocampus (Kitaichi et al, 2004(Kitaichi et al, , 2006Muraki et al, 2001;Wegener et al, 2003) and additively increased the elevating effect of SSRI and MAOI on extracellular 5-HT concentrations (Kitaichi et al, 2006;Muraki et al, 2001). Furthermore, subchronic lithium increased the anxiolytic-like effect of SSRI and MAOI in contextual conditioned fear (Kitaichi et al, 2006;Muraki et al, 1999).…”
mentioning
confidence: 99%